Antibiotics Utilization and their Cost in Ayder Referral Hospital, Mekelle, Ethiopia (Global Journal of Medical Research, 2015)
Inappropriate use of antibiotics can potentially lead to antimicrobial resistance and increase the necessity to use more expensive antibiotics to treat common and life threatening infections. The major goal of this research was to determine antibiotics utilization and their cost among in-patients treated in Ayder Referral Hospital. An institution based cross-sectional study was conducted in medical, gynecology and obstetrics, and surgical wards from September to December, 2012. The prevalence of antibiotics use was 35.5%. Antibiotic therapy was found to be inappropriate in 137 patients (80.6%).
Keywords: irrational drug use; antibiotics; ayder referral hospital; cost; inpatients